Involvement of PaSNF1 in Fungal Development, Sterigmatocystin Biosynthesis, and Lignocellulosic Degradation in the Filamentous Fungus Podospora anserina - Li, Yuanjing; Yan, Pengfei; Lu, Xiaojie; Qiu, Yanling; Liang, Shang; Liu, Gang; Li, Shuangfei; Mou, Lin; Xie, Ning (Frontiers in Microbiology, 2020)
The SNF1/AMPK is a central regulator of carbon metabolism and energy production in the eukaryotes. In this study, the functions of the Podospora anserina SNF1 (PaSNF1) ortholog were investigated. The ΔPaSNF1 mutant displays a delayed development of mycelium and fruiting bodies, and fails to form ascospores. Expression of the PaSNF1 gene in the strain providing female organs in a cross is sufficient to ensure fertility, indicating a maternal effect. Results of environmental stress showed that ΔPaSNF1 was hypersensitive to stress, such as, osmotic pressure and heat shock, and resistant to fluconazole. Interestingly, the knockout of PaSNF1 significantly promoted sterigmatocystin (ST) synthesis, but suppressed cellulase (Filter Paperase, endoglucanase and β-glucosidase) activity. Further transcriptome analysis indicated that PaSNF1made positive regulatory effects on the expression of genes encoding cellulolytic enzymes. These results suggested that PaSNF1 may function in balancing the operation of primary and secondary metabolism. This study suggested that SNF1 was a key regulator concerting vegetative growth, sexual development and stress tolerance. Our study provided the first genetic evidence that SNF1 was involved in the ST biosynthesis and it may also be a major actor of lignocellulose degradation in P. anserina.